MEDIA AND GENDER STEREOTYPES: A RATIONAL DISCUSSION - Rai, Vinay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Gender Stereotyping has deepened its roots in society and is needed to be dealt with as early as possible. The media has a greater influence on the views of Gender. Media plays a vital role in the process of gendering by exposing male and female children to stereotypical masculine and feminine activities. The images of sexes many of which eternalize unrealistic, stereotypical, and limiting perceptions are being communicated by all the forms of media. This research paper provides an overview of how media leads to the under-representation of women, and how both men and women are being constantly sexualized on various media platforms.